2022
DOI: 10.1186/s12912-022-00905-2
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of home-visiting nurses toward risk management of patient safety incidents in Japan

Abstract: Background In situations of home care, patients and their family members must address problems and emergencies themselves. For this reason, home-visiting nurses (HVNs) must practice risk management to ensure that patients can continue receiving care in the comfort of their homes. The purpose of this study was to examine HVNs’ attitudes toward risk management. Methods This study adopted a qualitative description approach. Semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Limited access to paraclinical services like immediate access to laboratory or radiology services was another barrier to patient safety in the present study. Considering the above, it can be argued that the home environment suffers from serious limitations for delivering optimal care, especially for elderly patients with chronic diseases, which should be addressed properly according to the patient’s condition before comprising the patient safety 50 51…”
Section: Discussionmentioning
confidence: 99%
“…Limited access to paraclinical services like immediate access to laboratory or radiology services was another barrier to patient safety in the present study. Considering the above, it can be argued that the home environment suffers from serious limitations for delivering optimal care, especially for elderly patients with chronic diseases, which should be addressed properly according to the patient’s condition before comprising the patient safety 50 51…”
Section: Discussionmentioning
confidence: 99%
“…The items pertaining to the HVNs’ attitudes toward patient safety were created in reference to the content of an interview survey the researchers had conducted in advance [ 12 ]. For the initial items, we sought the opinions of university faculty members and graduate students majoring in community nursing and made revisions to determine whether they showed attitudes toward patient safety.…”
Section: Methodsmentioning
confidence: 99%
“…Another important aspect of ensuring patient safety is consulting information from incident reports related HVNs to and home care. However, one study [ 2 ] found that among the 70% HVNs who experienced incidents, 40% did not report their incidents. Further, notably, most incidents that occur in the absence of HVNs are not reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations